DETERMINANTS OF MANUFACTURING FIRM VALUE: AN EMPIRICAL STUDY ON THE INDONESIA STOCK EXCHANGE - Tiana Fenny Krisdina; Ahmad Andy Adinegara; Maman Nurachman (Center for Economic Studies Universitas Katolik Parahyangan, 2026)
This study aims to investigate the determinants of manufacturing firm value on the Indonesia Stock Exchange during the 2021-2024 period. By integrating signaling and trade-off theories, this research examines the impact of liquidity, leverage, and profitability on Price to Book Value (PBV). Utilizing a quantitative approach with purposive sampling, a final sample of 185 observations was analyzed using multiple linear regression via SPSS 25. The empirical results indicate that, simultaneously, liquidity, leverage, and profitability significantly influence firm value. Partially, the study finds that liquidity has no significant effect on firm value, suggesting that investors perceive high cash holdings as unproductive assets. Conversely, both leverage and profitability exert a positive and significant impact, with profitability emerging as the most dominant predictor. These findings imply that market appreciation is primarily driven by a firm's earnings capacity and strategic capital structure. This research provides valuable insights for investors and corporate managers in optimizing financial performance to maximize shareholder wealth in emerging markets.